Peran Katekis Dalam Menghidupi dan Mengembangkan Kabar Baik Melaui Injil di Dunia Modern - Damiana Ley; Teresia Noiman Derung (Jurnal Teologi Injili dan Pendidikan Agama, 2025)
This research examines the function of catechists in carrying out and spreading the good news through evangelism in modern times. Catechists, who act as teachers and guides in the faith, hold the important responsibility of conveying Christ's teachings to the faithful, including not only the transmission of theological information but also the development of character and spirituality. Catechists are individuals trusted and appointed by the Church to proclaim God's work of salvation. In this situation, digital media is very important as a tool to reach the younger generation and the wider community. In the postmodern era, where skepticism is increasingly widespread, catechists are expected to become more creative and innovative in their approaches. The testimony of the catechist's life is also considered a major factor that can influence the acceptance of the Gospel message by the congregation. Their life in the community must be able to be an example or role model for the people. In addition, this research explores the role of catechists in developing people's faith through religious education programs that are relevant to everyday life. Challenges faced by catechists, such as lack of support from the Church community and limited resources, coincide with efforts to increase the effectiveness of evangelism. The method used is qualitative.